The cow in the parking lot [compact disc, unabridged] : a zen approach to overcoming anger - Scheff, Leonard (HighBridge, 2010)
Leonard Scheff is a lawyer and Buddhist who has used what he has learned from Buddhism to teach others to handle their anger. His approach helps the listener identify the unmet demands that trigger anger and what we can do to disslove our anger, laugh at ourselves, deal with the anger of others, and transform our anger into compassion.